2022
DOI: 10.3390/medicina58070873
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Heart and Lung Doses According to Tumor Bed Boost Techniques in Early-Stage Left-Sided Breast Cancer: Simultaneous Integrated Boost versus Sequential Boost

Abstract: Background and Objectives: The boost dose to the tumor bed after whole breast irradiation (WBI) can be divided into sequential boost (SEQ) and simultaneous integrated boost (SIB). SIB using modern radiation therapy (RT) techniques, such as volumetric modulated arc therapy, allow the delivery of a highly conformal dose to the target volume and has a salient ability to spare at-risk organs. This study aimed to compare the radiation dose delivered to the heart and lungs according to boost technique and tumor bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In our study, we found that the SIB plan signi cantly reduced V5, V10, V15, V30, and V40 compared to the SEQ plan, indicating its superiority in reducing low-dose exposure to normal lung tissue. This aligns with the ndings from Kim et al [15]. Additionally, we observed a decrease in Dmean for the left lung in the SIB plan compared to the SEQ plan, consistent with previous research.…”
Section: Dosimetric Evaluationsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found that the SIB plan signi cantly reduced V5, V10, V15, V30, and V40 compared to the SEQ plan, indicating its superiority in reducing low-dose exposure to normal lung tissue. This aligns with the ndings from Kim et al [15]. Additionally, we observed a decrease in Dmean for the left lung in the SIB plan compared to the SEQ plan, consistent with previous research.…”
Section: Dosimetric Evaluationsupporting
confidence: 93%
“…At the same time, the PTVtb was 49.6 Gy, (total of 16 fractions). The PTV prescription dose of the SEQ H-VMAT plan for WB was 42.5 Gy, a total of 16 fractions, followed by 4 fractions consecutive increase doses in PTV for TB, with 2.66 Gy for each fraction [15]. According to the prescription dose requirements and organ-endangering dose limitations, at least 95% of PTVs are required to reach the prescribed dose, optimizing the irradiation dose for the whole heart, atrium, ventricle, coronary artery, heart valve, lung, spinal cord, and contralateral breast.…”
Section: Treatment Planningmentioning
confidence: 99%